2009
DOI: 10.1158/0008-5472.fbcr09-c11
|View full text |Cite
|
Sign up to set email alerts
|

Abstract C11: CD117 and Stro-1 identify osteosarcoma stem cells associated with metastasis and chemotherapy-drug resistance

Abstract: Osteosarcoma, the most common bone cancer, is the second highest cause of cancer-related death in children and adolescents. Approximately 90% of cases show micro-metastasis at diagnosis, making systematic chemotherapy the first choice of treatment. Despite intensive chemotherapy, the survival rate for high-grade osteosarcomas remains only 50-80%. The inadequacy of current treatments may result from the inability to effectively target cancer stem cells (CSCs) or tumor initiating cells (TI-Cs) of osteosarcoma. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recently, our group (40) showed in vitro as well as in vivo evidence of the high metastatic potential of osteosarcoma TICs (Table 1). Using murine primary and established cell lines, we demonstrated that mesenchymal stem cell markers CD117 and Stro-1, but not markers such as CD44, CD105, and CD49b, were preferentially expressed in spheres and doxorubicin-resistant cells.…”
Section: Osteosarcomamentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group (40) showed in vitro as well as in vivo evidence of the high metastatic potential of osteosarcoma TICs (Table 1). Using murine primary and established cell lines, we demonstrated that mesenchymal stem cell markers CD117 and Stro-1, but not markers such as CD44, CD105, and CD49b, were preferentially expressed in spheres and doxorubicin-resistant cells.…”
Section: Osteosarcomamentioning
confidence: 99%
“…CD117/c-kit is a 145 kDa transmembrane glycoprotein and is expressed in both haematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs). Recently, our group has shown that CD117 in combination with another MSC-specific marker Stro-1 can identify osteosarcoma TICs (40). Thus, TICs can be identified from various types of cancer using stem cell surface markers.…”
Section: Stem Cell Surface Markersmentioning
confidence: 99%
See 1 more Smart Citation